STATUS PENGUSAHAAN MINYAK ATSIRI DAN FAKTOR-FAKTOR TEKNOLOGI PASCA PANEN YANG MENYEBABKAN RENDAHNYA RENDEMEN MINYAK - Yuhono, JT.; Suhirman, Sintha (Pusat Penelitian dan Pengembangan Perkebunan, 2006)
The Enterprise Status of Essential Oil and The Factors of Post Harvest Technology That Caused Its The Low of Oil RendementIn generally, essential crops were cul-tivated by farmer with limited of capital, large area and using a simple destilation, with the result that quality and rendement still lower. The research aimed to known status of essential oil enterprise and the factors that caused its rende-ment of oil still low. The research was conducted on April - July 2004 in 7 Provinces of producti-on centra of essential oil with make use of case study methods. The result indicated that conditi-on of destilation in 7 Provinces in generally still used the simple processing technology, which a kettle of its destilation made from waste drum or iron plate, except in Province of Banten, West Java, and Central Java have already make use of the good technology of destilation (patchouly and cananga). The factors that caused the low of oil rendement and quality are materials contruc-tion of destilation tools, preparations of raw materials and destilation process.